Analisis Pertumbuhan Dan Kontribusi Dana Bagi Hasil Pajak Dari Provinsi Terhadap Pendapatan Daerah Di Kabupaten Musi Banyuasin - Farida Aryani; Candra Romanda; Mona Lestari Utami (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2020)
The growth of the Provincial Tax Revenue Sharing Fund of the Musi Banyuasin Regency from 2016 to 2020 shows the Unsuccessful criteria. The increase in growth occurred in 2018 and 2019 by 12.32% and 5.29%, The decline in the growth of Revenue Sharing Funds occurred in the 2017 Tax and amounted to 55.99%, this was due to a decrease in income in the tax sector, namely cigarette taxes and in in 2017 the provincial government paid the receivables in the previous year but not as much as the payment of receivables in 2016. Funds in 2020 again decreased by 31.28% from the previous year, this is due to a decrease in Provincial Tax DBH revenue in almost all tax sectors such as the tax sector vehicles on water, transfer fees for motorized vehicles, transfer fees for vehicles on water, motor vehicle fuel tax, surface water extraction and utilization tax, heavy equipment vehicle tax and transfer fees for heavy equipment vehicles. Only motor vehicle taxes and cigarette taxes experienced an increase in Provincial Tax DBH income in 2020. The contribution of the Provincial Tax Revenue Sharing Fund to Musi Banyuasin Regency regional income was included in the Medium criteria by contributing to the Musi Banyuasin Regency regional income an average of 35.82 %. In 2016 the Tax Revenue Sharing Fund contributed 50.92%, in 2017 there was a decrease in the contribution of 27.69%, for the revenue sharing fund in 2017 it increased by 12.03% but this year the Provincial government paid DBH receivables not amounted to 2016 so that the transfer realization was not as big as 2016, in 2018 there was an increase in the contribution of provincial tax revenue-sharing funds by 9.74% from the previous year, this was due to an increase in provincial tax-sharing revenue-sharing in all tax sectors. In 2019, there was another increase in the contribution of tax revenue-sharing funds due to increased income in all tax sectors. In 2020 there was a 15.7% decrease in contribution from the previous year, this was due to a decrease in provincial tax revenue-sharing funds, such as in the water vehicle tax sector, motor vehicle transfer fees, surface water collection and utilization taxes, heavy equipment vehicle taxes and fees. Behind the name of heavy vehicles, only motor vehicle taxes and cigarette taxes experienced an increase in income. Based on the analysis that has been done, it shows that the contribution of the Tax Revenue Sharing Fund from the Province to regional income is still quite low and it is hoped that the government can maintain and even increase its achievements every year.